Effect of polyphenols from Ascophyllum nodosum seaweeds on the rheology and digestion of corn starch gels and gluten-free bread features - Leticia Montes; Maria Santamaria; Raquel Garzon; Cristina M. Rosell; Ramón Moreira (Heliyon, 2024)
The main objective of this work is to study the effect of polyphenols, from the brown seaweed Ascophyllum nodosum, on the structure and digestion behaviour of gels at two corn starch concentrations (1.95 and 5.00% w/w) as well as the structure, color and texture features of crumbs from gluten-free breads. Adsorption isotherms of polyphenols on native and gelled starches were carried out and modelled by means of Langmuir and Henry models, respectively. The formation and characteristics of tested gels were rheologically monitored by means of heating ramp, time sweep at high temperature, cooling ramp and frequency sweep at 25 °C. Elastic modulus values decreased with the presence of polyphenols. Additionally, the polyphenols significantly decreased the digestion rate, measured by both chemical and rheological procedures, and the final concentration of digested starch. Finally, the presence of polyphenols in breads increased the hardness and chewiness values and decreased the cohesiveness and resilience values as well as the crumb hardening during storage.